Advances in brain-computer interface controlled functional electrical stimulation for upper limb recovery after stroke - Yidan Zhang; Yuling Gao; Jiaqi Zhou; Zhenni Zhang; Min Feng; Yong Liu (Brain Research Bulletin)
Stroke often results in varying degrees of functional impairment, significantly affecting patients' quality of daily life. In recent years, brain-computer interface-controlled functional electrical stimulation has offered new therapeutic approaches for post-stroke rehabilitation. This paper reviews the application of BCI-FES in the recovery of upper limb function after stroke and explores its underlying mechanisms. By analyzing relevant studies, the aim is to provide a theoretical basis for rehabilitating upper limb function post-stroke, promote BCI-FES, and offer guidance for future clinical practice.